Effect of Increased Blood Flow Velocity on Fatigue in Hemodialysis Patients - Hossein Kakhki Jaghargh; Maryam Bagheri; Nahid Aghebati; Habibollah Esmaily (Mashhad University of Medical Sciences, 2020)
Background: Fatigue is one of the outcomes of reduced dialysis adequacy (DA) in patients undergoing hemodialysis (HD). Accordingly, increased blood flow velocity (BFV) can be one of the strategies to enhance DA and reduce fatigue. Aim: This study aimed to determine the effect of increased BFV on fatigue in HD patients. Method: This two-group randomized clinical trial was conducted on 74 HD patients attending 17-Shahrivar Hospital and Shafa Dialysis Center, Mashhad, Iran, during 2018. The intervention group was subjected to 25 and 50 rounds, which were added to the mean value calculated for dialysis machine velocity. Considering the control group, the rounds of the machine were set as those mean of the first two sessions. Fatigue was measured using the standardized Multidimensional Fatigue Inventory. The blood urea nitrogen (BUN) level and DA were analyzed after the 1st, 8th, and 14th sessions. The data were analyzed in SPSS software (version 16) through independent t-test, repeated measures analysis of variance (ANOVA), Mann-Whitney U test, and Chi-square test. Results: The mean ages of the control and intervention groups were 57.16±13.81 and 55.86±13.56 years, respectively. The results of repeated measures ANOVA showed that fatigue in the intervention group had significantly dropped during HD sessions, compared to the control group. Moreover, these patients obtained better DA (P˂0.001). Implications for Practice: Increased BFV of the dialysis machine leads to improved DA, BUN removal, and reduced fatigue in HD patients, which can be recommended to nurses as an effective strategy.